Preparation of Hydrochlorothiazide Nanoparticles for Solubility Enhancement - Vaculikova, Eliska; Cernikova, Aneta; Placha, Daniela; Pisarcik, Martin; Peikertova, Pavlina; Dedkova, Katerina; Devinsky, Ferdinand; Jampilek, Josef (Molecules (Basel, Switzerland), 2016)
Nanoparticles can be considered as a useful tool for improving properties of poorly soluble active ingredients. Hydrochlorothiazide (Class IV of the Biopharmaceutical Classification System) was chosen as a model compound. Antisolvent precipitation-solvent evaporation and emulsion solvent evaporation methods were used for preparation of 18 samples containing hydrochlorothiazide nanoparticles. Water solutions of surfactants sodium dodecyl sulfate, Tween 80 and carboxymethyl dextran were used in mass concentrations of 1%, 3% and 5%. Acetone and dichloromethane were used as solvents of the model compound. The particle size of the prepared samples was measured by dynamic light scattering. The selected sample of hydrochlorothiazide nanoparticles stabilized with carboxymethyl dextran sodium salt with particle size 2.6 nm was characterized additionally by Fourier transform mid-infrared spectroscopy and scanning electron microscopy. It was found that the solubility of this sample was 6.5-fold higher than that of bulk hydrochlorothiazide.
Keywords: velikost částic; hydrochlorothiazide; Surface-Active Agents; Solvents; Particle Size; Nanoparticles; scanning electron microscopy; Molecular Structure; solubility; dynamický rozptyl světla; Hydrochlorothiazide; Solubility; dynamic light scattering; infrared spectroscopy; rozpustnost; nanočástice; rozpouštědla; příprava léků; molekulární struktura; hydrochlorthiazid; nanoparticles; povrchově aktivní látky; Drug Compounding; Dynamic Light Scattering